A chemical study of the essential oil of Apium graveolens Linn. (Fam. Umbelliferae) - Ramos, Libertad (de Leon) 1946-
The dry fruits (seeds) of Apium graveolens L. (kintsai) gave upon steam distillation, an average yield of 1.2% essential oil. An average moisture content of 24% was obtained by the azeotropic distillation method. The fresh leaves and petioles of Apium graveolens L. (kintsai) and Apium graveolens L. var. dulce Pers. (celery) yielded upon distillation with steam, an average of 0.18% and 0.10%, respectively, of essential oil. The physical and chemical properties of the essential oil from kintsai seeds were determined. A comparative investigation of the constituents of the essential oils from the seeds of kintsai, the leaves and petioles of kintsai and celery, were undertaken by subjecting each oil separately to column chromatography and analyzing the oils and the resulting fractions individually by thin-layer chromatography, gas chromatography and infrared spectrophotometry. The results of the analysis showed the presence of d-limonene and &-pinene as the major and minor constituent, respectively, in the three essential oils.